Pegcetacoplan compared with supportive care for 26 weeks for participants with paroxysmal nocturnal hemoglobinuria: a plain language summary - Ming Wong, Raymond Siu; Navarro-Cabrera, Juan Ramon; Comia, Narcisa Sonia; Goh, Yeow Tee; Idrobo, Henry; Kongkabpan, Daolada; Gómez-Almaguer, David; Al-Adhami, Mohammed; Ajayi, Temitayo; Alvarenga, Paulo; Savage, Jessica; Deschatelets, Pascal; et al. (Future Rare Diseases, 2024)
In the PRINCE study, adults with paroxysmal nocturnal hemoglobinuria (PNH) who had not recently taken a C5 complement inhibitor medicine received pegcetacoplan or supportive care. Pegcetacoplan reduced hemolysis better than supportive care and was well tolerated.